Indonesia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper looks at links between Indonesia's commodities sector and recent corporate sector and banking system performance. On the production side, oil and natural gas output has fallen since 2010, with existing fields in decline, while production of coal, palm oil, and rubber output has increased steadily. Recent trends in commodity exports have had a significant impact on corporate revenues and profits. For corporations operating in the nonrenewable commodities sector, liabilities and debt ratios have increased significantly in recent years. This paper highlights that risks facing the commodities sector will likely stay elevated in the near term, given slowing growth of several major trading partners and the outlook for lower commodity prices.